Nilai Filosofis Makanan Tradisional Etnik Betawi untuk Pendidikan Karakter - Humaira, Adinda Hanna; Suswandari, Suswandari; Gunawan, Rudy (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Traditional food not only serves to fulfill biological needs, but also contains cultural values that reflect the identity of an ethnic group, including the Betawi ethnic group. Amidst the currents of globalization and modernization, traditional culinary heritage is increasingly marginalized, even though it contains a philosophy of life, social values, and moral teachings that have the potential to be transformed into character education. This study aims to identify the types of traditional Betawi ethnic food in the Kemang area as the research location, including snacks, heavy meals, and drinks, and analyze philosophical values that can support character formation. This study uses a Qualitative approach with the Ethnography method by Spradley, the data analysis technique used is "12 Step-by-Step Forward Research Flow". This technique is able to explore the deep meaning of symbols, values, and cultural practices embedded in traditional Betawi ethnic food in a sequential and planned manner. By following stages such as determining informants to writing ethnography, the author not only understands the physical form of food. But, also the philosophical values and cultural meanings inherent in it. The research results show that the philosophical values inherent in traditional Betawi food and beverages have significant potential for inclusion in character education. Particularly in contextual learning based on local culture, traditional food and beverages can serve as a medium for instilling character values, such as mutual cooperation, responsibility, simplicity, and a love of culture.